The Local Government Creation Under Democracy - GBEREVBIE, Christopher; MUKORO, Akpomuvire (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
The primary goal of creating local governments under democracy is to implement democratic ideals at the grassroots level. Establishing a freely chosen local government council is intended to improve grassroots service delivery in an efficient and effective manner. In order to do this, the study looks at how local governments are formed in Nigeria under the democratic system. The existing body of relevant literature was reviewed. The old-fashioned design was applied. The study used secondary data that was subjected to a qualitative content analysis using the content analysis technique. The analysis revealed that the establishment of local governments, whether democratic or military, has not fulfilled its constitutional mandate. The councils of the local governments that are democratically elected are not particularly noteworthy. Among other recommendations made by the study were to stop the state government from interfering with local governments' finances and to stop encouraging more local governments to step up during this critical period by reviewing the allocation upward, which would allow them to continue providing the services that the grassroots population needs.